The development of a strategic risk analysis framework for interconnected surface transportation systems. (1st January 2011) - Leventakis, George; Sfetsos, Athanasios; Moustakidis, Nikolaos; Gkrizis, Vasileios; Nikitakos, Nikitas
Transportation networks are centre to the daily lives of millions of citizens around the world. By design, they are open and freely accessible systems that may be exploited for malicious purposes. Transportation networks, especially in dense urban environments, are integral part of larger synergistic systems forming a network of networks. The present paper introduces a strategic risk assessment framework for assessing risks stemming from security incidents in interconnected, interdependent and heterogeneous transportation networks. The developed framework attempts to build upon existing operational risk analysis frameworks of transportation operators and the organisation of major events. The derived risk assessment approach is designed to estimate risk in interconnected transportation networks and ultimately estimate a holistic risk in the network of networks.